2007
DOI: 10.1093/eurheartj/ehm244
|View full text |Cite
|
Sign up to set email alerts
|

Carotid intima-media thickness by B-mode ultrasound as surrogate of coronary atherosclerosis: correlation with quantitative coronary angiography and coronary intravascular ultrasound findings

Abstract: Carotid atherosclerosis correlates better with coronary atherosclerosis when both circulations are investigated by the same technique (ultrasound) using the same parameter (IMT). This supports the concept that carotid IMT is a good surrogate marker of coronary atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
104
0
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(119 citation statements)
references
References 58 publications
6
104
0
9
Order By: Relevance
“…However, in most analyses SAD was more robustly associated to IMT and PWV compared to WC. There were also significant associations between both abdominal obesity and inflammatory markers, as well as between 10 inflammatory markers and markers of subclinical organ damage. Interestingly, inflammatory markers were associated to PWV but not to IMT.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, in most analyses SAD was more robustly associated to IMT and PWV compared to WC. There were also significant associations between both abdominal obesity and inflammatory markers, as well as between 10 inflammatory markers and markers of subclinical organ damage. Interestingly, inflammatory markers were associated to PWV but not to IMT.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, in view of its correlation with coronary atherosclerosis and its capacity to predict incident coronary events, carotid IMT has been proposed as a surrogate marker of coronary atherosclerosis (10). Also pulse wave velocity (PWV) measured by tonometry provides a noninvasive estimate of arterial stiffness and is an independent predictive risk factor for all-cause mortality and cardiovascular mortality (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…18) However, cardiovascular events are not determined only by increased carotid IMT, as 75% of thrombi in the carotid are caused by rupture, and 30% to 35% of coronary thrombi are caused by erosion. 19) The correlation between carotid IMT and future cardiac events remains modest at best, 20) but carotid atherosclerosis estimated by B-mode ultrasound is still a valuable predictor of myocardial infarction as a simple, noninvasive approach. 21) Clinically, increasing attention has been paid to carotid IMT.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies from around the world have demonstrated that there is a strong correlation between the risk of cerebrovascular diseases and the characteristics of the carotid artery wall [1][2][3]. Ultrasound examination is a widely used diagnostic tool for assessing and monitoring the plaque buildup via the carotid window.…”
Section: Introductionmentioning
confidence: 99%